Properties and Performance of Polycrystalline Cubic Boron Nitride. (12th January 2015) - Swab, Jeffrey J.; Vargas‐Gonzalez, Lionel; Wilson, Elizabeth; Warner, Eric
Abstract : Cubic boron nitride (CBN) is a lightweight (ρ = 3.45 g/cm 3 ) ceramic material that is harder than all materials except diamond. As harder ceramics tend to perform better as armor, this material is of interest to the military community. CBN is synthetically produced and is primarily used as an abrasive and in cutting tool applications. The properties (elastic modulus, strength, toughness, hardness, etc.) and ballistic performance of this material were determined and compared to a commercially available armor‐grade boron carbide (B4 C).